2017
DOI: 10.1176/appi.ajp.2016.16050627
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Ethyl Glucuronide-Based Contingency Management for Outpatients With Co-Occurring Alcohol Use Disorders and Serious Mental Illness

Abstract: Objective To determine if a contingency management intervention using the ethyl glucuronide (EtG) alcohol biomarker resulted in increased alcohol abstinence in outpatients with co-occurring serious mental illnesses. Secondary objectives were to determine if contingency management was associated with changes in heavy drinking, treatment attendance, drug use, cigarette smoking, psychiatric symptoms, and HIV-risk behavior. Method Seventy-nine (37% female, 44% non-white) outpatients with serious mental illness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 36 publications
4
86
0
Order By: Relevance
“…1). Although our published research demonstrates that uEtG > 499 ng/mL is associated with poor treatment response [20], unpublished analyses suggested that a lower cut-off of uEtG > 349 ng/mL predicts poor treatment response similar to a uEtG cut-off > 499 ng/ mL. The use of a lower cut-off of uEtG > 349 ng/mL cut-off will allow increase the number of potential participants randomized into the 3 CM conditions during the treatment phase.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). Although our published research demonstrates that uEtG > 499 ng/mL is associated with poor treatment response [20], unpublished analyses suggested that a lower cut-off of uEtG > 349 ng/mL predicts poor treatment response similar to a uEtG cut-off > 499 ng/ mL. The use of a lower cut-off of uEtG > 349 ng/mL cut-off will allow increase the number of potential participants randomized into the 3 CM conditions during the treatment phase.…”
Section: Methodsmentioning
confidence: 99%
“…However, variables that differ between groups at baseline and during the induction phase will be used as covariates in subsequent analyses, as will baseline measures that co-vary with the outcome measures. This is a strategy of preliminary analysis that we and several other teams in the area of CM and addiction treatment have utilized for several decades [20,21,23,50–53]. …”
Section: Analytic Planmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some (Harasymiw and Bean 2007;Wetterling et al 2014) but not all (Bertholet et al 2014;Liangpunsakul et al 2010) studies suggest that physiological biomarkers can supplement patient self-report in identifying alcohol use in community samples, primary care, and other medical settings. Research also suggests that physiological biomarkers can be used to identify relapse to drinking (Mundle et al 1999) and to promote abstinence (McDonell et al 2017) or to demonstrate risk for alcohol-related behaviors such as driving while intoxicated (Maenhout et al 2014;Marques et al 2010) or health complications after liver transplant (Kollmann et al 2016;Piano et al 2014;Staufer et al 2011). Additional information on the rationale for using physiological biomarkers in the management of individuals with AUD can be found in the advisory from the Substance Abuse and Mental Health Services Administration (2012).…”
Section: Statement 3: Use Of Physiological Biomarkersmentioning
confidence: 99%